A Review on Mucormycosis - Somarouthu, Deepthi; Thota, Vasantha; Ampolu, Kalyani (International Journal of Scientific Research and Management (IJSRM), 2021)
Mucormycosis is a opportunistic fungal infection that occurs in patients who are immunocompramised. The fungus causing mucormycosis belongs to the class of zygomycetes and the order of mucorales. It is highly life-threatening mycotic infection that is characterised by angioinvasion, infarction, and tissue necrosis. The risk factors include uncontrolled diabetes mellitus in ketoacidosis, various forms of metabolic acidosis, treatment with corticosteroids, organ or bone marrow transplantation etc. The diagnosis is challenging and treatment should start as early as possible to decrease mortality. Diagnosis is based on symptoms such as, in case of sinusitis, sinus biopsies are required. Ear, nose and throat endoscopy should be done. Molecular identification of mucormycosis can help in confirming diagnosis and identify the fungus from genus to species level. Different techniques are as follows: DNA probes targeting 18S subunit, ITS1 sequencing after PCR with pan-fungal primers, 18S-targeted semi-nested PCR and real time PCR targeting cytochrome b gene. The therapeutic approach should be multimodal including anti-fungal agents, surgical debridement, and correction of underlying symptoms predisposing the patient to disease.